Best Answer

2x² - 18

Looking at it, you know that the first factors in each set are 2x and x.

(2x ± ?) (x ± ?)

Then guess and check to find 2 factors that when multipled together equal -18, but when plugged into the equation make the original statement true. In this case 6 and 3, however one or the other needs to be negative.

(2x + 6)(x - 3) OR (2x - 6)(x + 3)

Multiply it out to check your answer:

(2x + 6)(x - 3) = 2x² - 6x + 6x - 18

2x² - 6x + 6x - 18 = 2x² - 18

You would get the same result with (2x - 6)(x + 3)

Q: Factorise 2x to the power 2 -18?

Write your answer...

Submit

Still have questions?

Continue Learning about Math & Arithmetic

we factorise a number by finding the common factor. example: 2x+6 = 2 is the common factor the 2 is then put outside the bracket 2x+6 = 2(x+3)

2x + 7 + 5 = 2x + 12 = 2*x + 2*6 = 2*(x+6)

5x4 - 2x = x*(5x3 - 2) and that cannot be factorised further without invoking surds.

4

Use www.wolframalpha.com Enter factor 4x^2+8x-5 to receive the answer (2x-1)(2x+5)

Related questions

If you mean: 2x+10 then it is 2(x+5)

2x + 6 = 2(x+3)

we factorise a number by finding the common factor. example: 2x+6 = 2 is the common factor the 2 is then put outside the bracket 2x+6 = 2(x+3)

2x + 12 = 2*x + 2*6 = 2*(x + 6)

2x + 7 + 5 = 2x + 12 = 2*x + 2*6 = 2*(x+6)

It is 2(2x+3) when factorised

5x4 - 2x = x*(5x3 - 2) and that cannot be factorised further without invoking surds.

the GCF of each term is 2; so, you simply factor out a 2 from each term.---------------------------2x + 14factor out the 2 to get:2( x + 7 )

2 + 2x = 18 2x = 18 - 2 2x = 16 x = 8

4

2(2x-11)(3x+5)

X3 + 8= (x+2)(x2-2x+4)